Nursing Students' Perceptions of English as A Lingua Franca - Komilie Situmorang; Sandra Sembel (JEELS (Journal of English Education and Linguistics Studies), 2019)
Provoked by the Faculty of Nursing’s graduate career prospective, ‘nurse in international nursing services’, this study aimed to investigate the Englishes nursing students were in favour of and the Englishes they needed for their future career and to find out their perceptions toward English as a Lingua Franca (ELF). Taking the form of a case study, this study collected data through open-ended questionnaires and semi-structured interviews. The findings generally highlighted paradoxes in participants’ views of ELF. Students were found to be in favour of Standard English (SE), although in the future what they truly expected from patients was the intelligibility to create therapeutic conversation. Furthermore, the participants seemed to be aware of the variety of Englishes in existence but believed that SE should be taught in class. This study also found out that local accents speak for their cultural identity. Therefore, the implication of the study calls for attention to the potential benefits of introducing ELF and provides some recommendation of how ELF could be best introduced at classrooms.